Atomic-concentration diffusion governing integrated-territory graphene syntheses at catalyst–insulator interfaces. (June 2016) - Zhuang, Pingping; Lin, Weiyi; Tian, Bo; Zhang, Cankun; Zhao, Zhijuan; Shih, Tien-mo; Cai, Weiwei
Abstract: The Cu film is needed for catalysis purposes during graphene syntheses, and its presence leads to direct graphene growth on the Cu surface, thus requiring subsequent cumbersome transfer processes. It is plausible that atomic diffusion processes occurring through the Cu film can be controlled to harvest the graphene grown at the interface between the Cu film and the film-deposited substrate. In our study, we have materialized this possibility by optimally injecting the Ar/H2 plasma to remove the undesired surface graphene, facilitating the diffusion of active carbon (a–C) atoms and the growth of integrated interface graphene territories. Using both SEM and Raman spectroscopy, we observe conspicuous sharp G and 2D peaks, as well as absent D peaks with high continuities. Furthermore, this interface graphene exhibits high carrier mobilities ( μ p = 1117.5 cm 2 V −1 s −1 and μ e = 896.5 cm 2 V −1 s −1 ). Therefore, the identified mechanism can offer guides for electronic industries to synthesize high-quality graphene directly deposited on insulators.